Henry and Mudge and the careful cousin : the thirteenth book of their adventures - Rylant, Cynthia; Stevenson, Sucie (New York : Simon & Schuster Books for Young Readers, 1994)
At first Henry's very neat cousin doesn't like the cookies from under his bed or Mudge's slobbery kisses, but when they all play frisbee, she begins to enjoy her visit.
13
Keywords: Dogs -- Fiction; Cousins -- Fiction; Orderliness -- Fiction; Dogs -- Juvenile fiction; Cousins -- Juvenile fiction; Orderliness -- Juvenile fiction